(3GdaJMjI aj GdCYeGd GdLjHjIs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s ((3KZQ WfLI s)
(3ChdgG (B:s
(3hHYO , agPg QSGdI eNJUQI ai GdYed HGdQHY GdeLjH ai GdebOeI ai JSejI QSheg ChdgG GdeQcR hgh GdHNT GdPj ajg GdNjW s
(3BNQgG (B:s
(3hEf CdajJ eWGdYg ef eWGdY GdTQhb GdeSJbHd Hbi GdHGbi ef Gddjd YfO JhSWg aEf JSGhi GdHGbi MUI GdaLQ JhSW Chd hbJ GdaLQ hGddg CYde GfJgJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B54 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B188s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B216 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B484 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 - (3U (B187 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs